The Effectiveness of AI Based Microlearning Platforms through Vlog Content to Improve Arabic Listening Skills - Ganjar Yusup Sofian; Sutaman; R. Taufiqurrochman; Ahmad Fadhel Syakir Hidayat; Nukman Nukman (Institut Agama Islam Negeri Curup, 2026)
The rapid expansion of digital technology and Artificial Intelligence (AI) has significantly transformed learning practices in higher education, particularly in the development of foreign language listening skills. This quasi-experimental study examined the effectiveness of an AI-based microlearning platform integrating authentic Vlog content in improving Arabic listening comprehension. Sixty undergraduate students participated in a four-week, one-group pretest–posttest design. Data were collected through listening comprehension tests and classroom observations. The results revealed a statistically significant improvement in students' listening skills, with a large instructional effect, indicating a meaningful pedagogical impact. Although proportional learning gains were relatively low, this outcome reflected high initial proficiency levels rather than limited intervention effectiveness. Observation results confirmed high fidelity throughout the intervention. Overall, the findings support the integrating of microlearning, multimodal video input, and AI-driven adaptivity as a practical approach to enhancing Arabic listening skills in higher education.